Television memory on the pages of Intervalo magazine: relations with the reader and the new TV culture of the 1960s and 1970s in Brazil (Intercom - Brazilian Journal of Communication Sciences, 2023)
The accelerated urbanization and technological development of the 1960s implemented the era of mass communication in Brazil, characterized by the emergence of new consumption habits of material and symbolic goods. The magazine Intervalo (1963-1972) is an important example, as a communication device of an enthusiastic television vehicle, responsible for developing editorial strategies that created bonds with readers and influenced the formation of the television audience. This article intends, through Cultural Studies, to present and analyze such strategies and to understand what the agencies on the part of the magazine for the construction of a television ambiance are, as well as the dissemination of standards of values, behaviors, and social characteristics that, together, represent the memory of Brazilian television and the TV consumer society.
Keywords: Magazine Intervalo; Media History; Reader; Viewer; Television